Utilización de los rincones de lectura en el proceso de aprendizaje los niños de educación inicial subnivel II en la Unidad Educativa Darío C. Guevara - Amaiquema de Lucca, Ginger Lisbeth (2023)
In this present study, the use of reading corners in the learning process of children in Initial Education sublevel II in the “Darío C. Guevara” Educational Unit was investigated. The learning process was analyzed in the use of the reading corner as a primary factor for the intellectual development of the child. That is why it is necessary to provide activities in an environment conducive to the adequate development of these processes, whether through meaningful learning. In this research, an observation guide was carried out to know what the problems were, poor use of the reading corner was evident, so the child does not have a good result in the learning process. The research was of an explanatory and field type, because the information was collected at the scene, it is in a qualitative approach, the research technique was the interview with the teachers and an observation guide for the children to collect information that allowed us to demonstrate that the materials in the reading corner motivate children to have a good learning process, but in the institution they do not have enough material, that is, only the most common ones were found, the stories are not reconcilable with the age of the children in sublevel II, puppets that do not attract attention due to the state they are in, scarcity of fables, among others, given the lack of materials in the reading corner, the teacher has the initiative to investigate what the materials that are needed for the activities that are carried out when teaching in class to have a correct learning process.